Developing prosthetic artificial muscle actuator using dielectric elastomers - El-Hamad, Haneen Jawad Mahmoud (2016)
The loss of an upper limb can impair the ability to do even the simplest daily tasks. Robust prosthetic devices need to replicate the smooth movement, while maintaining the relatively high forces typical of the original limb. Dielectric elastomers (DEs) are potential candidates for actuating such prosthetic devices, however, DE materials are associated with material failure which limits their use as actuators. They also have been reported to generate low output force. This has limited DEs from being used for prosthetic devices that mainly require high output forces. This thesis proposes a conceptual design for a prosthetic arm, where the actuator is the DE material arranged in a suggested mechanism to generate high output force. A two-bar mechanism was assumed to represent the human arm. The flexion action of the elbow was achieved by a slider-crank mechanism connecting the two bars actuated by DEs membranes. The DE actuator mechanism comprised of the arrangement of 1000 parallel planar linear DE membranes in parallel to maintain high output force and reduce the tensile stress. An Analytic model was developed to analyze the output force of the designed mechanism for a range of input electric fields. An electrical model was developed to model electrodes resistance and DE membrane leakage current resistance. Material and mechanism‟s dimensions and parameters were mathematically optimized to produce the highest possible output force while maintaining the tensile stress and the input electric field below material failure points. An open loop system was designed to control the angular position of the arm. Mechanical and electrical power consumption calculations were carried out and the efficiency of the actuator and major energy dissipations were determined. The actuator‟s generated force counteracts a compressive mechanical force of 97 N which is higher than reported actuator designs for arm prosthetics and is comparable to human muscle output force for arm flexion estimated between 40 N to 116 N. The 1000 DE membranes arrangement led to a reduction of the compressive stress over the material to be (30 kPa) which is well below the break point of 690kPa. The stimulant input electric field that is below the dielectric strength of the material which is 40MV/m. The critical input electric field at which electromechanical instability failure occurs has been increased by 2.05 times the critical input of voltage induced strain only. A high input electric field of range of 31.287 MV/m to 33.837 MV/m, yet with a power consumption of 248 mW per membrane is convenient for use in prosthetic devices. The electromechanical efficiency is 55.7% and the loss is mainly due to viscous energy dissipation and current leakage. The 1000 DE membrane arrangement led to the generation of high output force with lower input electric fields and lower stress over the material. Therefore, this actuator‟s design could be used as a prosthetic arm actuator replacing conventional actuators provided that further steps of realization are taken.